THE NEEDS OF THE STUDENTS WHO ARE TAKING GRAMMAR (STRUCTURES) IV COURSE AT ENGLISH DEPARTMENT OF TARBIYAH FACULTY ACADEMIC YEAR OF 2012/2013 - Asfihana, Raida (English Department of Faculty of Tarbiyah and Teachers Training, 2013)
The studentsâ needs of English have been a never ending issue for recent years. It is always be an interesting topic to be discussed as well as investigated through a series of research. This following research report is a description of the studentsâ need of taking Grammar IV course at TarbiyahÂ Faculty of IAIN Antasari Banjarmasin. The students were asked to fill in a questionnaire dealing with their needs of taking that course. The result shows that they think that grammar mastery is important for them and they prefer to do much practice on TOEFL exercise (the section of Structures and`Written Expression) through this course.